Adaptive Evaluation: A Complexity-based approach to Systematic Learning for Innovation and Scaling in Development - Gokhale, Siddhant; Walton, Michael (CID Faculty Working Paper, 2023)
Nearly all challenges in international development tend to be complex because they depend on constantly evolving human behaviour, systems, and contexts, involving multiple actors, entities, and processes. As a result, both the discovery and scaling of innovations to address challenges in development often involve changes in system behaviour or even system-level transformation. This is rarely a linear process over time and can result in unexpected outcomes. Existing evaluation techniques commonly used in international development, including Randomized Control Trials (RCT) and quasi-experimental methods, are good at assessing specific effects of interventions but are not designed for the change processes inherent to innovation and scaling within a system. There is a need to reconstruct how we use existing measurement tools, techniques, and methodologies so that they capture the complexity of the environment in which an intervention or change occurs. We introduce Adaptive Evaluation, designed to learn at various levels of complexity while supporting the transformation needed to foster sustainable change. An Adaptive Evaluation uses three main approaches to work with complex questions—systems diagnosis, theorybased assessment of change processes, and iterative designs. An Adaptive Evaluation typically builds hypotheses from field-based interactions, emphasizes learning over testing, advocates open-mindedness with techniques, and appreciates the value of dialogue and participation in navigating complex processes. It can use RCT or similar techniques to analyse specific processes within a system or a development cycle, but these are embedded in a broader approach to assessment and interpretation. It is designed to be flexible and adjust to shifting contexts. Finally, an Adaptive Evaluation can be applied at any stage in a complex intervention's lifecycle, from the interpretation of the system and change processes to rapid experimentation, prototyping, and testing of select interventions, and then adaptation to different settings for impact at scale. This paper provides the theoretical basis for an Adaptive Evaluation—the main approaches, core ideology, process, and applications.

Evaluating complex interventions in international development - Masset, Edoardo; Shrestha, S.; Juden, M. (CEDIL Methods Working Paper 6, 2021)
This paper reviews promising methods for the evaluation of complex interventions that are new or have been used in a limited way. It offers a taxonomy of complex interventions in international development and draws on literature to discuss several methods that can be used to evaluate these interventions. Complex interventions are those that are characterised by multiple components, multiple stakeholders, or multiple target populations. They may also be interventions that incorporate multiple processes of behavioural change. While such interventions are very common and receive a large proportion of development aid budgets, they are rarely subject to rigorous evaluations. The CEDIL Methods Working Paper, ‘Evaluating Complex Interventions in International Development’, reviews promising methods for the evaluation of complex interventions that are new or have been used in a limited way. It offers a taxonomy of complex interventions in international development and draws on literature to discuss several methods that can be used to evaluate these interventions. The paper focuses its attention on methods that address causality and allow us to state conclusively whether an intervention works or not. It shows that several rigorous methods developed in different disciplines can be adapted and used to evaluate complex interventions in international development.

Evaluating complex interventions: What are appropriate methods? - Masset, Eduardo (CEDIL, 2022)
In the CEDIL Methods brief, ‘Evaluating complex interventions: What are appropriate methods?’ we identify four types of complex development interventions: long causal chain interventions, multicomponent interventions, portfolio interventions, and system-level interventions. These interventions are characterised by multiple activities, multiple outcomes, multiple components, a high level of interconnectedness, and non-linear outcomes.